Computed tomography and echocardiography in patients with acute pulmonary embolism: part 1: correlation of findings of right ventricular enlargement - Wake, Nicole; Kumamaru, Kanako K; George, Elizabeth; Bedayat, Arash; Ghosh, Nina; Gonzalez Quesada, Carlos; Rybicki, Frank J; Gerhard-Herman, Marie (Journal of thoracic imaging, 2014)
To evaluate the correlation between the computed tomography (CT)-derived right ventricle (RV) to left ventricle (LV) diameter ratio and the RV size determined by echocardiography in patients with acute pulmonary embolism. Consecutive CT pulmonary angiography examinations (August 2003 to May 2010) from a single, large, urban teaching hospital were retrospectively reviewed. For a cohort of 777 subjects who underwent echocardiography within 48 hours of the CT acquisition, the qualitative RV size (divided into 5 categories) extracted from the echocardiography report was correlated with the CT-derived RV/LV diameter ratio. There was moderate correlation (Spearman rank correlation coefficient=0.54, P<0.001) between the CT-derived RV/LV ratio and the RV size as determined by echocardiography. The correlation coefficient and the concordance rate were inversely related to the time difference between the acquisitions of the 2 modalities. CT and echocardiography findings to assess the RV size after acute pulmonary embolism have moderate correlation.